1999
DOI: 10.1088/0953-2048/12/1/007
|View full text |Cite
|
Sign up to set email alerts
|

Influence of growth rate on the structural orientation of YBCO superconducting films

Abstract: Superconducting films were grown by DC magnetron sputtering of a stoichiometric target at varied pressure (p =5-100 Pa) of argon/oxygen mixture and substrate (MgO(100), , ) temperature K. Film axis orientation and crystal quality were investigated using Raman spectroscopy and medium energy ion backscattering technique. The pressure and substrate temperature determine the growth rate and the crystallographic orientation of YBCO films. At a critical value of about 1.5-2.0 nm , films of mixed orientation are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Various forms of the overall reaction have been proposed in the literature, but there is ample evidence that the reaction path to the final epitaxial YBCO film is, however, complex, both chemically and topologically. The growth rate of the YBCO film is governed by T , P (H 2 O), and total pressure, , and it has been demonstrated that a careful adjustment of the process parameters is essential to control the microstructure and therefore the critical currents of the films …”
Section: Introductionmentioning
confidence: 99%
“…Various forms of the overall reaction have been proposed in the literature, but there is ample evidence that the reaction path to the final epitaxial YBCO film is, however, complex, both chemically and topologically. The growth rate of the YBCO film is governed by T , P (H 2 O), and total pressure, , and it has been demonstrated that a careful adjustment of the process parameters is essential to control the microstructure and therefore the critical currents of the films …”
Section: Introductionmentioning
confidence: 99%
“…From the energy standpoint, we believe that the inclined DWs are a consequence of competition between the elastic energy of a propagating surface, tending to keep it flat, and the DW energy. As the growth rate of a-b plane is much higher than that along the c-axis in YBCO [16], the a-axis oriented domains grow faster in the normal direction of the interface than the surrounding c-axis epitaxial film. This will cause convexes at the surface of the film, which may increase the surface energy.…”
Section: Resultsmentioning
confidence: 99%
“…As known, the c ⊥ -oriented structure is a metastable phase of the YBa 2 Cu 3 O 7 compound [22,29,32]. Formation of c -microblocks oriented in a different way leads to the development of block boundaries, i.e.…”
Section: Structure and Composition Of Ybco Filmsmentioning
confidence: 99%